2003
DOI: 10.1007/bf02849858
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of β-aescin from horse chestnut seed extract: Comparative clinical studies of two galenic formulations

Abstract: The bioavailability of beta-aescin--the main active constituent of horse chestnut seed extract--in a nonretarded test medication in comparison with that in a retarded reference formulation was evaluated in 2 randomized crossover clinical trials involving 18 healthy volunteers each. Serum concentration/time curves derived under steady-state conditions and pharmacokinetic parameters measured during both studies showed no significant difference between absorption rates for the retarded versus nonretarded preparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…According to the manufacturer, our St John's wort batch was comparable to that used by Gurley et al . However, a variation in bioavailability among herbal constituents in general can be expected, making some uncertainties in our estimation [18][19][20]. These estimates indicate that the lowest total concentration of St John's wort used in our hepatocytes, 8 μ g/ml, is in the same range as that obtained in plasma with a recommended dosing of St John's wort.…”
Section: Discussionmentioning
confidence: 95%
“…According to the manufacturer, our St John's wort batch was comparable to that used by Gurley et al . However, a variation in bioavailability among herbal constituents in general can be expected, making some uncertainties in our estimation [18][19][20]. These estimates indicate that the lowest total concentration of St John's wort used in our hepatocytes, 8 μ g/ml, is in the same range as that obtained in plasma with a recommended dosing of St John's wort.…”
Section: Discussionmentioning
confidence: 95%
“…In view of the possible relevance of b-escin in anticancer therapy, some formulations were tested in order to establish their effectiveness on the basis of bioavailability and bioequivalence (Bassler et al, 2003). The positive results strongly encourage pursuing new cure modalities, with treatments based on well-tolerated natural products.…”
Section: Applications To Health Promotion and Disease Preventionmentioning
confidence: 99%
“…Only bioavailability studies of escin presented under the form of extracts or mixtures have been reported [22,23]. It is known that pharmacokinetic studies of the herbal medicinal product help in linking data from pharmacological assays to clinical effects and also in designing rational dosage regimens [24].…”
Section: Introductionmentioning
confidence: 99%
“…Radioimmunoassay (RIA) methods have been developed to study the bioavailability of escin in human [22,23]. However, these methods possess some disadvantages such as low selectivity and complicated sample preparation procedures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation